Some Issues of the Formation of Environmental Thinking (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
So, what is the essence of ecological thinking? Ecological thinking today is most often defined as a sustainable understanding of the value of everything that nature gives us, the interconnection of all elements of the ecological system of a city, a region, the entire planet Earth, a sense of one's share of responsibility for ensuring that nature and the ecosystem are in order.